2021
DOI: 10.31015/jaefs.2021.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characteristics of Some Gilaburu (Viburnum Opulus L.) Genotypes

Abstract: Gilaburu is an important fruit species in terms of healthy effects, having potential for use as alternative medicine and suitable for industrial product processing. In this context, physico-chemical characteristics of three different gilaburu (Viburnum opulus L.) genotypes grown under the ecological conditions of Kayseri, Turkey were determined. In addition, correlations among the investigated characteristics were calculated and their potential to be handled together was revealed. According to results, Fruit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In another study, it was reported that the fruit length value ranged from 1.04 mm to 11.85 mm, and the fruit weight values were between 0.40 g and 1.80 g (Ozrenk et al, 2011). The study conducted with genotypes taken from the same region but different district as in the current study, fruit length was determined between 7.65 mm and 8.81 mm, while fruit weight ranged from 0.30 g to 0.37 g (Polat et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was reported that the fruit length value ranged from 1.04 mm to 11.85 mm, and the fruit weight values were between 0.40 g and 1.80 g (Ozrenk et al, 2011). The study conducted with genotypes taken from the same region but different district as in the current study, fruit length was determined between 7.65 mm and 8.81 mm, while fruit weight ranged from 0.30 g to 0.37 g (Polat et al, 2021).…”
Section: Resultsmentioning
confidence: 99%